PEDAGOGICAL CONDITIONS FOR IMPLEMENTING CONTINUOUS SPIRITUAL EDUCATION USING SOURCES OF NATURAL VALUES IN THE EDUCATIONAL PROCESS - Ortiqova Nargiza Akramovna (Sciental Journals Publishing, 2025)
The article describes the essence of the content of educational values and their sources in educational institutions, effective methods, forms, and techniques for using them in the educational process, and the spiritual and moral qualities that should be formed in students through educational values.
Keywords: Educational values, sources, educational process, method, form, method, means, spiritual and moral qualities, pedagogical conditions.